The joy at the Last Judgement according to the Heidelberg Catechism Question 52 - Busch, Eberhard (HTS teologiese studies, 2014)
In this contribution, the author reflects on Question 52 of the Heidelberg Catechism where it asks: ‘What comfort is it to you that Christ “shall come to judge the living and the dead”?’ The author points out possible sources from which this formulation stems, that is, Articles 86 and 87 in John Calvin’s Catechism from 1545. God is described as a compassionate judge. Even more: the One who is the last judge, was also judged and had paid for our sins. In a dialectical fashion we discover a God who is just, but also merciful. The Reformed tradition did not follow a dead-end where it is taught that God shows us grace instead of righteousness. Had God proceeded in this way, he would only mean things well, but he would not make them well. The realisation of God being just and merciful leads to joy and repentance. The contribution ends with a discussion of the final separation of the just and evil.